Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1042/bsr20193404
|View full text |Cite
|
Sign up to set email alerts
|

MiR-141-3p overexpression suppresses the malignancy of osteosarcoma by targeting FUS to degrade LDHB

Abstract: Osteosarcoma (OS) is a common malignant bone cancer. Lactate dehydrogenase B (LDHB) has been revealed to act as a tumor promoter in several cancers. It is also revealed to be correlated with poor prognosis in OS, but its molecular mechanism in OS remains veiled. Our work illustrated that LDHB was overexpressed in OS tissues and cells, and it could enhance cell proliferation, migration, and invasion in OS. Subsequently, it was confirmed that fused in sarcoma (FUS) could bind with LDHB to positively regulate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…In addition, Wen et al (11) reported that circ_HIPK3 promoted OS cell proliferation, migration and invasion by regulating miR-637 and HDAC4 signaling. As a tumor suppressor-related miRNA, miR-141-3p has been reported to serve as a tumor suppressor in several types of cancer, including OS (24)(25)(26)(27). With use of a Circular RNA Interactome database, the present study predicted that circ-LRP6 may have a binding site with miR-141-3p, which was confirmed by dual luciferase assay.…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…In addition, Wen et al (11) reported that circ_HIPK3 promoted OS cell proliferation, migration and invasion by regulating miR-637 and HDAC4 signaling. As a tumor suppressor-related miRNA, miR-141-3p has been reported to serve as a tumor suppressor in several types of cancer, including OS (24)(25)(26)(27). With use of a Circular RNA Interactome database, the present study predicted that circ-LRP6 may have a binding site with miR-141-3p, which was confirmed by dual luciferase assay.…”
Section: Discussionsupporting
confidence: 62%
“…Previous studies have demonstrated that miRNAs can bind to the 3′-UTRs of target genes to achieve post-transcriptional regulation, thereby modulating the occurrence and progression of related diseases ( 20 - 25 , 45 , 63 ). In the present study, TargetScan bioinformatics analysis and luciferase assays confirmed that miR-141-3p bound to the 3′-UTR of HDAC4 and HMGB1.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…miR-141-3p expression is reported to be decreased and act as a tumor suppressor in several types of tumors. For example, miR-141-3p expression is downregulated in osteosarcoma; miR-141-3p targets FUS to degrade L-lactate dehydrogenase B chain to reduce the degree of malignancy of osteosarcoma ( 22 ). In addition, miR-141-3p suppresses colorectal cancer cell proliferation, migration and invasion by targeting TNF receptor-associated factor 5 ( 23 ).…”
Section: Discussionmentioning
confidence: 99%